A new lighting method for cultural materials using selective chromatic light. (May 2022) - Gargano, M; Scotuzzi, S; Angelin, EM; Santilli, O; del Hoyo-Meléndez, JM; Ludwig, N
Lighting is a critical component in a museum environment because, together with temperature, relative humidity and pollutants, it is one of the damaging factors able to produce long‐term, cumulative and irreversible photodegradation processes. To correctly preserve artworks, limiting illuminance and exposure is recommended, allowing on one side the preservation of the object, but on the other limiting the display of the object, especially for sensitive materials. The aim of this research was to develop, evaluate and compare a new lighting method for paintings and other cultural materials to improve the experience of the objects whilst reducing the risks from exposure. The idea is based on the use of selective chromatic light where the component of the spectrum absorbed by the materials is removed. This absorption is the principal cause of photodegradation. The proposed lighting system can be obtained by combining different types of projection systems together with filtering using an appropriate light source. Six methods of light projection have been compared for two mock-ups simulating real artworks with high and medium light sensitivity. The efficiency of illumination increased from 30% to 111% compared to standard lighting systems. Light stability tests were additionally performed, finding reduced colour changes compared to traditional lighting systems.